IIT (BHU) to get DRDO centre of excellence, MoU signed at DefExpo - Singh, Binay (The Times of India, 2022)
Varanasi: A DRDO Industry Academia-Centre of .. Read more at: http://timesofindia.indiatimes.com/articleshow/95023509.cms?utm_source=contentofinterest&utm_medium=text&utm_campaign=cppst
Keywords: DRDO; DEFEXPO